2001
DOI: 10.1007/s002320010072
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Amino Acid Exchange across b0,+-like System in Chicken Brush Border Jejunum

Abstract: In the small intestine, cationic amino acids are transported by y(+)-like and b(0,+)-like systems present in the luminal side of the epithelium. Here, we report the characterization of a b(0,+)-like system in the apical membrane of the chicken jejunum, and its properties as an amino acid exchanger. Analysis of the brush border membrane by Western blot points out the presence of rBAT (protein related to b0,+ amino acid transport system) in these membranes. A functional mechanism for amino acid exchange across t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 24 publications
3
41
0
Order By: Relevance
“…In the present study, the inhibition obtained with NEM confirms the participation of system y ϩ on L-Met uptake in the absence of Na ϩ . System b 0,ϩ is a tertiary transport system that exchanges extracellular cationic amino acids and L-cystine for intracellular neutral amino acids in a Na ϩ -independent way (30), with a higher binding affinity for the extracellular substrate (48). Finally, system L is a Na ϩ -independent transporter that preferentially recognizes large neutral amino acids with branched or aromatic side chains, as well as BCH (9).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the inhibition obtained with NEM confirms the participation of system y ϩ on L-Met uptake in the absence of Na ϩ . System b 0,ϩ is a tertiary transport system that exchanges extracellular cationic amino acids and L-cystine for intracellular neutral amino acids in a Na ϩ -independent way (30), with a higher binding affinity for the extracellular substrate (48). Finally, system L is a Na ϩ -independent transporter that preferentially recognizes large neutral amino acids with branched or aromatic side chains, as well as BCH (9).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the important roles attributed to HATs, only a few studies have addressed the structure-function relationships of these transporters: (i) most HATs are obligate antiporters with a 1:1 stoichiometry (14), and a sequential mode of exchange has been proposed for system b 0,ϩ (15); (ii) light subunits appear to be sufficient for transport activity, as demonstrated for b 0,ϩ AT (16); (iii) using xCT as a model for the light subunits, a membrane topology with 12 transmembrane segments and with a re-entrant loop between transmembrane segments 2 and 3 has been reported (17); and (iv) the xCT residues His 110 and Cys 327 have been shown to be crucial for function (17,18), whereas the cystinuria-specific mutation A354T inactivates b 0,ϩ AT (16). Similarly, structure-function studies on the APC superfamily as a whole have been very limited and primarily related to membrane topology studies and the identification of relevant residues for substrate interaction (19 -21).…”
mentioning
confidence: 99%
“…It has been shown that system b 0,ϩ from the chicken small intestine shows a sequential exchange mechanism compatible with the formation of a ternary complex (46). If this applies to the expressed b 0,ϩ AT-rBAT complex, then export and import pathways should co-exist simultaneously in the proposed functional unit (i.e.…”
Section: Discussionmentioning
confidence: 99%